PENGARUH STRUKTUR KEPEMILIKAN, LEVERAGE, RETURN ON ASSETS, DAN SIZE TERHADAP KEBIJAKAN DIVIDEN DENGAN GROWTH SEBAGAI VARIABEL MODERASI - Ida Putri Damayanti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2015)
This research aims to analyze the effect of ownership structure, leverage, return on assets (ROA), and size to dividend policy with growth as moderating. Sample taken using purposive sampling method, with a sample of 11 of the 136 companies listed on the Indonesia Stock Exchange in 2011-2013 period. Methods of data analysis using multiple regression analysis and MRA with interaction test approach. The results of research shows that the managerial ownership structure and public ownership structure had a positive effect and not significantly influence the Dividend Payout Ratio. Institutional ownership structure , leverage , and size had a negative effects and not significantly influence the Dividend Payout Ratio. ROA had a negative effects and significantly influence the Dividend Payout Ratio. While growth is not capable to moderating influence of ROA and size to the Dividend Payout Ratio. Keywords: Ownership Structure, Leverage, ROA, Size, Growth, DPR